Radiographic examination in the diagnosis of a curious case associating odontoma to agenesis and supernumerary teeth - FREIRE,Jéssica de Oliveira Alvarenga (2021)
ABSTRACT Developmental disorders of human dentition may result in various abnormalities according to etiologic agents and the developmental period involved. The size, shape and number of teeth may be affected. Dental abnormalities can occur singly or in multiples in an individual and may or may not be associated with syndromes. Complementary radiographic examinations are valuable for diagnosis, especially in lesions that are asymptomatic and detected only through examination. The present study is intended to report a case of an incidental finding in panoramic radiography of an odontoma, a supernumerary tooth and permanent tooth agenesis in the same non-syndromic individual. According to the literature, the association of hypodontia and hyperdontia (called concomitant hypo-hyperdontia) is most common. The association of hyperdontia and odontoma is uncommon but still reported. However, regarding the association of hypodontia and odontoma no reports were found, as well as the association of the three pathologies.